1999
DOI: 10.1097/00006454-199902000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Community-wide outbreak of enteroviral illness caused by echovirus 30: a cross-sectional survey and a case-control study

Abstract: Echovirus 30 caused substantial morbidity during this community outbreak caused by person-to-person spread. Household contacts, day-care centers and playgrounds were prominent risk factors for transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Children under 15 years old accounted for 80% of the patients. Comparable distribution patterns were found during previously reported outbreaks, which occurred in different geographical areas [Sawyer et al, 1994;Khalfan et al, 1998;Reintjes et al, 1999]. Leonardi et al [1993] reported a different age distribution with peak incidence in younger children, but this is not uncommon in enterovirus infections.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Children under 15 years old accounted for 80% of the patients. Comparable distribution patterns were found during previously reported outbreaks, which occurred in different geographical areas [Sawyer et al, 1994;Khalfan et al, 1998;Reintjes et al, 1999]. Leonardi et al [1993] reported a different age distribution with peak incidence in younger children, but this is not uncommon in enterovirus infections.…”
Section: Discussionsupporting
confidence: 54%
“…The role of echovirus 30 in the etiology of this disease has been known since the virus was first isolated in 1958 [Plager and Dechler, 1963]. The distribution of recent meningitis outbreaks caused by echovirus 30 strongly suggests that infections are widespread [Leonardi et al, 1993;Drebot et al, 1994;Rice et al, 1995;Lopez-Alcala et al, 1997;Gorgievski-Hrisoho et al, 1998;Khalfan et al, 1998;Reintjes et al, 1999;Uysal et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…An outbreak of echovirus 30 meningitis has occurred in Switzerland in the summer of 1996 [21]. Reintjes et al [15] reported the echovirus 30 meningitis outbreak in Germany in 1997. In Turkey, we detected an echovirus 30 aseptic meningitis outbreak during the summer of 1999 [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…All samples were collected in the acute phase of the disease. Enteroviral meningitis was defined as isolation of enterovirus from CSF and/or stool samples [4,15].…”
Section: Methodsmentioning
confidence: 99%
“…Most frequently, the infection is asymptomatic or subclinical; however, severe and life-threatening forms are not rare (18). E30 has recently been a common cause of meningitis in many countries (4,5,7,9,12,14,19) and was a subject of several epidemiological studies (2,15,21); therefore, many sequences for the VP1 genome region are available in GenBank for comparison. Previously, however, most studies of E30 epidemiology were conducted by using only the VP1 genome region.…”
mentioning
confidence: 99%